2012
DOI: 10.1152/ajpgi.00535.2011
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of the NADPH oxidase NOX1 in the pathogenesis of 5-fluorouracil-induced intestinal mucositis in mice

Abstract: . Potential role of the NADPH oxidase NOX1 in the pathogenesis of 5-fluorouracil-induced intestinal mucositis in mice. Am J Physiol Gastrointest Liver Physiol 302: G1133-G1142, 2012. First published March 7, 2012 doi:10.1152/ajpgi.00535.2011.-Although NADPH oxidase 1 (NOX1) has been shown to be highly expressed in the gastrointestinal tract, the physiological and pathophysiological roles of this enzyme are not yet fully understood. In the present study, we investigated the role of NOX1 in the pathogenesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 44 publications
5
55
0
Order By: Relevance
“…Inhibition of ROS production by apocynin, an antioxidant and a nonselective NOX inhibitor in leukocytes (Heumuller et al, 2008), reduced the severity of colonic inflammation (Mouzaoui et al, 2014;Ramonaite et al, 2014). We also reported that NOX1-deficient mice exhibited resistance to intestinal mucositis induced by an anticancer agent, 5-fluorouracil (Yasuda et al, 2012). Thus, the role for NOX1-derived ROS in the pathogenesis of gut inflammation has been controversial.…”
Section: Introductionmentioning
confidence: 85%
“…Inhibition of ROS production by apocynin, an antioxidant and a nonselective NOX inhibitor in leukocytes (Heumuller et al, 2008), reduced the severity of colonic inflammation (Mouzaoui et al, 2014;Ramonaite et al, 2014). We also reported that NOX1-deficient mice exhibited resistance to intestinal mucositis induced by an anticancer agent, 5-fluorouracil (Yasuda et al, 2012). Thus, the role for NOX1-derived ROS in the pathogenesis of gut inflammation has been controversial.…”
Section: Introductionmentioning
confidence: 85%
“…32,33) In this study, HST inhibited completely 5-FU-induced diarrhea, although HST inhibited partially gene expression of CXCL1, protein levels of ELA2 and MPO in vivo. While further studies are necessary to clarify the difference, these findings may indicate that HST also inhibits 5-FUinduced apoptosis, resulting in attenuation of diarrhea.…”
Section: Discussionmentioning
confidence: 49%
“…27) The pathogenesis of 5-FU-induced intestinal mucositis remains unclear, but is considered to be a consequence of various processes, including abnormal inflammation and apoptosis, together with cellular hypoproliferation and direct cytotoxicity. 28) We demonstrated that apoptosis in the intestinal crypt was caused by the upregulation of TNF-α-induced caspase-3/8 activations. 29) Ramosetron and ondansetron clearly suppressed the upregulation of TNF-α expression and subsequent caspase-3/8 activations in the intestinal crypt in response to 5-FU.…”
Section: Anti-intestinal Inflammatory Effects Of the 5-ht 3 Receptor mentioning
confidence: 85%